An overview of the effects of oil theft on the mangrove and wildlife ecosystems in the Niger Delta Zone : Review - Gbuvboro Anthonia Ejirohene (International Journal of Multidisciplinary Research and Growth Evaluation, 2024)
Mangroves have a positive ecological impact that supports the way of life for people who live along coastlines everywhere. They provide food and shelter to a number of animal populations, including wading birds and seabirds. Aside from that, many Nigerians, particularly those who reside along the coast, rely heavily on mangroves as a source of housing, fuel, and medicine. Constructed from a network of many creeks, the heart of the Niger Delta holds the largest mangrove swamp in Africa and the third largest in the world. Mangroves are important to the local economy and ecology wherever they are located in the Niger Delta. Mangroves provide such important purposes, yet they are losing vegetation at a rate of 1.7% per year on average; this issue is made worse by poor administration and fish smoking-related tree chopping. Even though the Niger Delta is home to a wide variety of natural species, the prestigious International Union for the Conservation of Nature (IUCN) does not yet recognize this area of exceptional ecology. Oil is crucial to the advancement of modern societies, due to its wide spread usage in manufacturing, transportation, and energy across the globe. However, oil leaks from drilling rigs, shipwrecks, and crude oil theft cause extensive, uncontrollable ecological harm in addition to destroying the functions that aquatic ecosystems serve. Coastal wetlands are still vulnerable to significant short term effects from oil, but the potential for recovery and its long-term effects, however, are less well known. This paper discusses the environmental assessments that are currently being published regarding the impact of oil on mangrove habitats. Furthermore, worldwide oil traffic is always increasing since the country's "mangrove biodiversity of the Niger delta region are regarded as the worst ruined in the globe." Since mangroves are often identified as places of importance for both maintenance and conservation, and since they are particularly sensitive to oil spills, the government should launch, The Mangrove Action Project (MAP), an international initiative to encourage mangrove preservation.
Effects of Mangrove Deforestation
Keywords: Mangrove forests; Niger delta zone; Biodiversity; oil-spillage; Conservation initiative